2017
DOI: 10.21037/jtd.2017.02.21
|View full text |Cite
|
Sign up to set email alerts
|

Should aggressive thoracic therapy be performed in patients with synchronous oligometastatic non-small cell lung cancer? A meta-analysis

Abstract: Background: We performed a meta-analysis to compare overall survival (OS) outcomes in patients with synchronous oligometastatic non-small cell lung cancer (NSCLC) who underwent aggressive thoracic therapy (ATT) with those who did not. Methods: A systematic review of controlled trials of ATT on survival in synchronous oligometastatic NSCLC was conducted. Hazard ratio (HR) for the main endpoint OS was pooled using a fixed-effects model. Subgroup analysis was performed in patients with single organ metastases, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 41 publications
1
52
0
Order By: Relevance
“…Theoretically, local control of the primary and metastatic tumor can reduce the intra‐thoracic disease burden and symptoms and might result in a better OS . This notion is supported by a study of extensive‐stage SCLC .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Theoretically, local control of the primary and metastatic tumor can reduce the intra‐thoracic disease burden and symptoms and might result in a better OS . This notion is supported by a study of extensive‐stage SCLC .…”
Section: Discussionmentioning
confidence: 83%
“…It has been shown that using RT to control primary and metastatic tumors can reduce intra‐thoracic disease burden, bronchial/vascular compression, and pulmonary symptoms . In addition, local control of primary and metastatic tumors might result in better OS . Recently, a phase III randomized controlled trial (RCT) showed that thoracic radiotherapy (TRT) also improved OS of patients with extensive‐stage small cell lung cancer (SCLC) who responded to chemotherapy .…”
Section: Objectivesmentioning
confidence: 99%
“…Some studies have analyzed oligometastatic disease (4,(6)(7)(8)(9)(10) and pleural dissemination in stage IV NSCLC (2,3). However, there are few reports that deal only with stage IV NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with NSCLC stage IV, if we select complete resection of the primary lesion as the initial treatment, an important consideration is whether local therapy, such as surgical resection or radiotherapy, is possible for the metastasis. These issues have been considered in both prospective and retrospective studies on oligometastasis (4,(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation